A Clinical Evaluation of the ALGES™ (hefilcon A) Bifocal Contact Lens - Gross, M.L (Canadian Journal of Optometry, 2021)
A new, soft bifocal contact lens design is described and its performance is assessed on the basis of sustained wearing time, refraction, acuity for near and far, k readings and pupil diameter. Recommendations are made to help improve success. Characteristics of successful and unsuccessful users are listed.